Изучение накопления и выведения ⁶⁵Zn черноморской водорослью Ulva rigida Ag. в связи с ее ростом - (:unkn) unknown (Киев : Наукова думка, 1978)
Экспериментально и на математических моделях изучался обмен и накопление ⁶⁵Zn черноморской Ulva rigida в связи с ее ростом в различных условиях освещенности. Измерение прироста и уровня накопления радионуклида производилось на живых образцах водоросли. Обнаружен а зависимость между накоплением ⁶⁵Zn и скоростью роста Ulva rigida. Накопление и обмен радиоактивного цинка удовлетворительно описывается камерной математической моделью, две камеры которой отражают кинетику обменных процессов, а третья — накопление ⁶⁵Zn в необменном фонде. Установлено, что потребление цинка на рост может достигать 30% обмениваемого количества.
Studies in Accumulation and Removal of ⁶⁵Zn by the Black Sea Alga Ulva rigida Ag. in Connection with Its Growth
Metabolism and accumulation of ⁶⁵Zn by the green alga Ulva rigida were studied in connection with its growth by means of experiments and methods of mathematical modelling. A dependence between the ⁶⁵Zn accumulation and the growth is found in Ulva rigida. It is shown that the ⁶⁵Zn metabolism in the alga is described satisfactorily by the chamber model, where two chambers show kinetic of the metabolic processes and the third one ⁶⁵Zn accumulation in the nonexchangable found of the alga. It is established that zinc uptake for growth may reach 30% of the zinc total amount exchanged by the alga.